2016
DOI: 10.1186/s40249-016-0170-5
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden and its associated factors of hospitalized patients infected with A (H7N9) virus: a retrospective study in Eastern China, 2013–2014

Abstract: BackgroundH7N9 continues to cause human infections and remains a pandemic concern. Understanding the economic impacts of this novel disease is important for making decisions on health resource allocation, including infectious disease prevention and control investment. However, there are limited data on such impacts.MethodsHospitalized laboratory-confirmed H7N9 patients or their families in Jiangsu Province of China were interviewed. Patients’ direct medical costs of hospitalization were derived from their hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 18 publications
0
28
1
Order By: Relevance
“…The lost earnings of non‐working days of patients, caregivers and visitors were evaluated as $184.3, $184.3 and $95.3, respectively. These lost earnings were significantly higher than that of HFMD cases in Shanghai and lower than that of H7N9 patients in Jiangsu Province (Huo et al, ; Wang et al, ). Our study also revealed that 99.1% of patients had health insurance, but only 25.8% of costs of SFTSV infection were covered by reimbursement.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The lost earnings of non‐working days of patients, caregivers and visitors were evaluated as $184.3, $184.3 and $95.3, respectively. These lost earnings were significantly higher than that of HFMD cases in Shanghai and lower than that of H7N9 patients in Jiangsu Province (Huo et al, ; Wang et al, ). Our study also revealed that 99.1% of patients had health insurance, but only 25.8% of costs of SFTSV infection were covered by reimbursement.…”
Section: Discussionmentioning
confidence: 96%
“…The median economic burden of SFTSV infection was $4,323.9 and lower than H7N9 patients in China (Huo et al, ). This might be due to longer hospitalization duration of H7N9 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, due to the brand recognition and expectation, when Chinese patients were switched from domestic drug (i.e., generics) to imported (joint venture) drugs, they usually reported a better drug efficacy (Ge and Zhu, 2007). However, as a vast, whether in unbalanced developed countries or in low-to-middle income countries, the medical resource is limited (Xu, 1990; Huo et al, 2016). We cannot offer all patients with imported (joint venture) drugs nor should we with good quality domestic drug.…”
Section: Introductionmentioning
confidence: 99%